2019
DOI: 10.1021/acs.est.9b02098
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Pathology of Plastic Ingestion in Marine Birds and Relationships with Blood Chemistry

Abstract: Pollution of the environment with plastic debris is a significant and rapidly expanding threat to biodiversity due to its abundance, durability, and persistence. Current knowledge of the negative effects of debris on wildlife is largely based on consequences that are readily observed, such as entanglement or starvation. Many interactions with debris, however, result in less visible and poorly documented sub-lethal effects, and as a consequence, the true impact of plastic is underestimated. We investigated the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
60
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(62 citation statements)
references
References 63 publications
2
60
0
Order By: Relevance
“…Fish are likely key vectors in the vertical and horizontal movement of plastic in the ocean, and may accumulate sublethal physical and chemical effects from ingested plastic (Lavers et al, 2019; Rochman et al, 2013), yet the impacts of plastic debris on marine communities and ecosystems are still mostly unknown (Bucci et al, 2020). Current evidence for humans ingesting plastic directly from fish remains scant, but there is growing concern (Barboza et al, 2018; Carbery et al, 2018; Lusher et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Fish are likely key vectors in the vertical and horizontal movement of plastic in the ocean, and may accumulate sublethal physical and chemical effects from ingested plastic (Lavers et al, 2019; Rochman et al, 2013), yet the impacts of plastic debris on marine communities and ecosystems are still mostly unknown (Bucci et al, 2020). Current evidence for humans ingesting plastic directly from fish remains scant, but there is growing concern (Barboza et al, 2018; Carbery et al, 2018; Lusher et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…During this time, microbial diversity and metabolic functions (i.e., lipid metabolism and glycolysis) were significantly altered. In wild‐caught flesh‐footed shearwaters ( Ardenna carneipes ), an endangered seabird in Australia, Lavers et al () observed a correlation between blood chemistry parameters (lowered blood calcium, heightened uric acid, cholesterol, and amylase) and reduced morphometrics (reduced body mass, wing length, culmen, and head + bill length) with the incidence of ingested plastic.…”
Section: Microplastic Uptake and Consequences In Biotamentioning
confidence: 99%
“…The presence of such items in bird nests can later result in the entanglement or ingesting by the chicks (or the parents), compromising nutritional requirements and development ( Tavares et al, 2016 ). Ingestion (even of relatively low quantities) of plastic debris by seabird Ardenna carneipes induced a significant negative effect on bird morphometrics and blood calcium levels, along with an increment in the uric acid, cholesterol, and amylase concentrations ( Lavers et al, 2019 ), revealing that it may have a negative impact on fitness. The presence of plastic waste in the nest's structure could also alter thermal and drainage properties, influencing reproductive success ( Thompson et al, 2020 ).…”
Section: Disposable Masks Can Directly Threaten Wildlifementioning
confidence: 99%